To add 9(k+1/3) + 10(1/2k-1), we can distribute the 9 and 10 to their respective terms inside the parentheses:
9(k+1/3) + 10(1/2k-1)
= 9k + 9(1/3) + 10(1/2k) - 10(1)
= 9k + 3 + 5k - 10
= 14k - 7
Therefore, the correct answer is 14k - 7.
Use the properties of operations to add 9(k+1/3)+10(1/2k−1) .(1 point)
Responses
1912k−23
19 Start Fraction 1 over 2 End Fraction k minus Start Fraction 2 over 3 End Fraction
14k+13
14 k plus 13
14k−7
14 k minus 7
14k−23
14 k minus Start Fraction 2 over 3 End Fraction
11 answers
Use the properties of operations to add 4(g−2)+(g+2) .(1 point)
Responses
5g
5 g
5g−6
5 g minus 6
5g−10
5 g minus 10
5g+10
Responses
5g
5 g
5g−6
5 g minus 6
5g−10
5 g minus 10
5g+10
To add 4(g-2) + (g+2), we can simplify each term inside the parentheses:
4(g-2) + (g+2)
= 4g - 8 + g + 2
Then, we can combine like terms:
= 4g + g - 8 + 2
= 5g - 6
Therefore, the correct answer is 5g - 6.
4(g-2) + (g+2)
= 4g - 8 + g + 2
Then, we can combine like terms:
= 4g + g - 8 + 2
= 5g - 6
Therefore, the correct answer is 5g - 6.
Use the properties of operations to subtract (h+k)−(2k−h) .(1 point)
Responses
2h−k
2 h minus k
2h+k
2 h plus k
−k
negative k
−2h−k
Responses
2h−k
2 h minus k
2h+k
2 h plus k
−k
negative k
−2h−k
To subtract (h+k) - (2k-h), we can distribute the negative sign to each term inside the second parentheses:
(h+k) - (2k-h)
= h + k - 2k + h
Then, we can combine like terms:
= h + h + k - 2k
= 2h - k
Therefore, the correct answer is 2h - k.
(h+k) - (2k-h)
= h + k - 2k + h
Then, we can combine like terms:
= h + h + k - 2k
= 2h - k
Therefore, the correct answer is 2h - k.
Use the properties of operations to subtract (p−3)−(2.4+2p) .(1 point)
Responses
−p−5.4
negative p minus 5.4
−p+5.4
negative p plus 5.4
p−5.4
p minus 5.4
3p−5.4
Responses
−p−5.4
negative p minus 5.4
−p+5.4
negative p plus 5.4
p−5.4
p minus 5.4
3p−5.4
To subtract (p-3) - (2.4 + 2p), we can distribute the negative sign to each term inside the second parentheses:
(p-3) - (2.4 + 2p)
= p - 3 - 2.4 - 2p
Then, we can combine like terms:
= p - 2p - 3 - 2.4
= -p - 2.4 - 3
= -p - 5.4
Therefore, the correct answer is -p - 5.4.
(p-3) - (2.4 + 2p)
= p - 3 - 2.4 - 2p
Then, we can combine like terms:
= p - 2p - 3 - 2.4
= -p - 2.4 - 3
= -p - 5.4
Therefore, the correct answer is -p - 5.4.
Subtract: 2(k−4)−3(2k−1) .(1 point)
Responses
8k−11
8 k minus 11
−6k−18
negative 6 k minus 18
−4k−11
negative 4 k minus 11
−4k−5
Responses
8k−11
8 k minus 11
−6k−18
negative 6 k minus 18
−4k−11
negative 4 k minus 11
−4k−5
To subtract 2(k-4) - 3(2k-1), we can distribute the 2 and 3 to their respective terms inside the parentheses:
2(k-4) - 3(2k-1)
= 2k - 8 - 6k + 3
Then, we can combine like terms:
= 2k - 6k - 8 + 3
= -4k - 5
Therefore, the correct answer is -4k - 5.
2(k-4) - 3(2k-1)
= 2k - 8 - 6k + 3
Then, we can combine like terms:
= 2k - 6k - 8 + 3
= -4k - 5
Therefore, the correct answer is -4k - 5.
thanks all them were right!!!!!!!!!!👌👌👌👍👍👍😁
You're welcome! I'm glad I could help. If you have any more questions, feel free to ask.